Why is satisfaction from pro-environmental behaviors increasing in costs? Insights from the rational-choice decision-error framework - Heinz Welsch (University of Oldenburg, Department of Economics, 2023)
The literature on subjective well-being (SWB) and the environment has found robust evidence of positive net marginal SWB from pro-environmental behavior (PEB), that is, positive marginal SWB net of the associated costs in terms of money, time and effort (Finding 1). Accordingly, people could increase their SWB (utility) by behaving more pro-environmentally. In addition, net marginal SWB was found to be larger with respect to more costly than with respect to less costly PEBs (Finding 2). Finding 1 is at odds with rational choice theory's demand that marginal utility be equalized with marginal costs, that is, net marginal utility be zero. The finding can be (and has been) explained by decision error, that is, a failure in forecasting the well-being consequences of an act of choice. This paper uses the rational-choice decision-error framework to show that if (i) observed levels of PEB are the result of rational choice and (ii) there is positive net marginal SWB at observed PEB levels due to decision error, then net marginal SWB from a PEB is increasing in its marginal costs. The ability of the rational-choice decision error framework to explain not only Finding 1 but Finding 2 provides empirical support for that framework.
Keywords: Q21; I31; D90; D11; D12; 330; pro-environmental behavior; subjective well-being; decision error; rational choice; affective forecasting